Did national holidays accelerate COVID-19 diffusion during the first phase of the pandemic in Bangladesh? - Mohammad Radid Khan; Sayem Mottakin; Md. Ahsan Kabir; Md. Enamul Hoque; Mohammad Ruhul Amin; Md. Harunur Rashid; Md. Shariful Islam (Intelektual Pustaka Media Utama, 2023)
Bangladesh registered 20,117,32 confirmed cases of COVID-19 and the death toll crossed the grim milestone of 29,323 across the country as of August 31st, 2022. Despite the enforcement of stringent COVID-19 measures, the country witnessed an accelerated diffusion of coronavirus cases during the national events, inclusive of short festivals, in 2020. The present study aims to examine the association between these national holidays and the COVID-19 trasmission rate in Bangladesh. We employed a mathematical model and calculated the instantaneous reproduction number, Rt, of the 64 districts in Bangladesh to check the dynamics of COVID-19 diffusion. The comprehensive analysis shows a notable escalation of Rt value and thus the enhanced transmission rate in Dhaka and in all industrialized cities during the major events such as, garments reopening and religious holidays in Bangladesh. We further showcase the COVID-19 diffusion explicitly in Dhaka Division at the first phase of the pandemic in Bangladesh. Based on our analysis, a set of measures, including restricted public mobility and the celebration of festivals, alongside improving the public’s awareness of the situation, has been recommended to evade the future pandemic risks while running the national festival activities in Bangladesh.